How do you simplify #(4+sqrt50)-(3-sqrt(8)) #?

2 Answers
Mar 31, 2018

Answer:

#=1+7sqrt2#

Explanation:

#sqrt50=5sqrt2# and #sqrt8=2sqrt2#

Equation becomes #(4+5sqrt2)-(3-2sqrt2)#

#=4+5sqrt2-3+2sqrt2#

#=1+7sqrt2#

Mar 31, 2018

Answer:

#(4+sqrt50)-(3-sqrt8)=1+7sqrt2#

Explanation:

#(4+sqrt50)-(3-sqrt8)#

#sqrt50=sqrt(25xx2)=sqrt25xxsqrt2=5sqrt2#

#sqrt8=sqrt(4xx2)=sqrt4xxsqrt2=2sqrt2#

#(4+sqrt50)-(3-sqrt8)=(4+5sqrt2)-(3-2sqrt2)#

#=4+5sqrt2-3+2sqrt2#

#=(4-3)+(5sqrt2+2sqrt2)#

#=1+7sqrt2#

#(4+sqrt50)-(3-sqrt8)=1+7sqrt2#